Inflammatory regulatory T cells in the microenvironments of ulcerative colitis and colon carcinoma. (2nd August 2016) - Kryczek, Ilona; Wang, Lin; Wu, Ke; Li, Wei; Zhao, Ende; Cui, Tracy; Wei, Shuang; Liu, Yan; Wang, Yin; Vatan, Linda; Szeliga, Wojciech; Greenson, Joel K.; et al.
ABSTRACT: Foxp3 + CD4 + regulatory T (Treg) cells are thought to express negligible levels of effector cytokines, and inhibit immune responses and inflammation. Here, we have identified a population of IL-8 + Foxp3 + CD4 + T cells in human peripheral blood, which is selectively increased in the microenvironments of ulcerative colitis and colon carcinoma. Phenotypically, this population is minimally overlapping with IL-17 + Foxp3 + CD4 + T cells, and is different from IL-8 − Foxp3 + CD4 + T cells in the same microenvironment. 40–60% of IL-8 + Foxp3 + CD4 + T cells exhibit naive phenotype and express CD127, whereas IL-8 − Foxp3 + CD4 + cells are basically memory T cells and express minimal CD127. The levels of CXCR5 expression are higher in IL-8 + Foxp3 + cells than in IL-8 − Foxp3 + cells. IL-2 and TGFβ induce IL-8 + Foxp3 + T cells. Exogenous Foxp3 expression promotes IL-8 + Foxp3 + T cells and inhibits effector cytokine IFNγ and IL-2 expression. Furthermore, Foxp3 binds to IL-8 proximal promoter and increases its activity. Functionally, IL-8 + Foxp3 + T cells inhibit T cell proliferation and effector cytokine production, but stimulate inflammatory cytokine production in the colon tissues, and promote neutrophil trafficking through IL-8. Thus, IL-8 + Foxp3 + cells may be an "inflammatory" Treg subset, and possess inflammatory and immunosuppressive dual biological activities. Given their dual roles and localization, these cells may be in a unique position to support tumor initiation and development in human chronic inflammatory environment.